Silver nanoparticles enhanced luminescence and stability of CsPbBr3 perovskite quantum dots in borosilicate glass. Issue 4 (2nd January 2020) - Zhang, Ke; Zhou, Dacheng; Qiu, Jianbei; Long, Zhangwen; Zhu, Rui; Wang, Qi; Lai, Junan; Wu, Hao; Zhu, Congcong
Abstract: Series of silver nanoparticles (NPs) embedded CsPbBr3 quantum dots (QDs) glass was synthesized via the melt‐quench method. Ag NPs and CsPbBr3 QDs coexist in the TEM image of the Ag‐doped glass sample. Photoluminescence (PL) spectra show that the 0.1 molar ratio Ag2 O‐doped sample had a PL intensity 2.37 times than the undoped sample. This increase is generated by localized surface plasmon resonance coupling between the Ag NPs and CsPbBr3 QDs. Excessive Ag doping weakens the PL intensity due to spectral self‐absorption of the Ag NP surface plasmon resonance (SPR). Self‐adsorption of SPR is detrimental to luminescence properties because it increases the amount of photogenerated charge carriers, which proceed through nonradiative relaxation pathways. In addition, stability results of Ag NP‐doped‐CsPbBr3 QD glass show that they have excellent stability. This study on Ag NP‐doped‐CsPbBr3 QD glass provides a new idea for the future development of perovskite QD optoelectronic devices.